SITE RESPONSE CHARACTERISTICS OF H/V SPECTRUM BY MICROTREMOR SINGLE STATION OBSERVATIONS AT PALU CITY, INDONESIA - Pyi Soe Thein; Subagyo Pramumijoyo; Kirbani Sri Brotopuspito; Wahyu Wilopo; Junji Kiyono; Agung Setianto (Geological Engineering Department Universitas Gadjah Mada, 2015)
In this study, we estimated predominant period of an H/V spectrum in Palu City, Indonesia, by using microtremor single station observations. Sulawesi Island, eastern Indonesia, is located at the junction between the converging Pacific-Philippine, Indo- Australian Plates and the Eurasian Plate. One of the major structures in Central Sulawesi is the Palu- Koro Fault system, which extends NNW-SSE direction and cross-cuts Sulawesi along more than 300 km from the North Sulawesi trench passing southward through Palu Bay then turn to the southeast, connecting to the Matano and Lawanopo Faults and further eastward both faults join to Tolo trench. Several earthquakes have been known along Palu-Koro Fault system such as Gimpu earthquake (1905), Kulawi earthquake (1907), Kantewu earthquake (1934), and offshore Donggala earthquake (1968) which caused tsunami that destroyed 800 houses and killed 200 people at Donggala district. Palu City, located at the northern tip of Palu depression, is a capital of the Central Sulawesi Province. It is located in the active seismic zone of the Palu-Koro fault. Spectral ratios for horizontal and vertical motion (H/V) from single-station microtremor records were used to identify the predominant periods of the ground vi- brations. Understanding the parameters of predominant period[s] and seismichazard is important for mitigation and environmental planning of the Palu region. Keywords: H/V spectrum, predominant period[s], microtremor single station observation